Thymoquinone protects rat liver after partial hepatectomy under ischaemia/reperfusion through oxidative stress and endoplasmic reticulum stress prevention. (19th June 2018) - Bouhlel, Ahlem; Bejaoui, Mohamed; Ben Mosbah, Ismail; Hadj Abdallah, Najet; Ribault, Catherine; Viel, Roselyne; Hentati, Hassen; Corlu, Anne; Ben Abdennebi, Hassen
Summary: Ischaemia reperfusion (I/R) is associated with liver injury and impaired regeneration during partial hepatectomy (PH). The aim of this study was to investigate the effect of thymoquinone (TQ), the active compound of essential oil obtained from Nigella sativa seeds, on rat liver after PH. Male Wistar rats were divided equally into four groups (n = 6) receiving an oral administration of either vehicle solution (sham and PH groups) or TQ at 30 mg/kg (TQ and TQ + PH groups) for 10 consecutive days. Then, rats underwent PH (70%) with 60 minutes of ischaemia followed by 24 hours of reperfusion (PH and TQ + PH groups). Alanine aminotransferase (ALT) activity and histopathological damage were determined. Also, antioxidant parameters, liver regeneration index, hepatic adenosine triphosphate (ATP) content, endoplasmic reticulum (ER) stress and apoptosis were assessed. In response to PH under I/R, liver damage was significantly alleviated by TQ treatment as evidenced by the decrease in ALT activity ( P < .01) and histological findings ( P < .001). In parallel, TQ preconditioning increased hepatic antioxidant capacities. Moreover, TQ improved mitochondrial function (ATP, P < .05), attenuated ER stress parameters and repressed the expression of apoptotic effectors. Taken together, our results suggest that TQ preconditioning could be an effective strategy to reduce liver injury after PH under I/R. The protective effects were mediated by the increase of antioxidant capacities and the decrease of ER stress and apoptosis.